Self-reported Antiretroviral Adherence: Association With Maternal Viral Load Suppression in Postpartum Women Living With HIV-1 From Promoting Maternal and Infant Survival Everywhere, a Randomized Controlled Trial in Sub-Saharan Africa and India. (1st January 2023) - Nevrekar, Neetal; Butler, Kevin; Shapiro, David E.; Atuhaire, Patience; Taha, Taha E.; Makanani, Bonus; Chinula, Lameck; Owor, Maxensia; Moodley, Dhayendre; Chipato, Tsungai; McCarthy, Katie; Flynn, Patricia M.; et al.
Abstract : Introduction: Optimal adherence to antiretroviral therapy (ART) is crucial to promoting maternal–infant health. Setting: Fourteen sites in 7 countries within sub-Saharan Africa and India. Methods: The multicomponent, open-label strategy PROMISE trial enrolled breastfeeding mother–infant pairs not meeting in-country criteria for maternal ART (mART) initiation in the postpartum component within 5 days of delivery. Randomization was to mART versus infant NVP (iNVP) prophylaxis. Infants in the mART arm also received 6 weeks of iNVP. Self-reported adherence was assessed in a secondary analysis. Time-to-event analyses were performed to explore the association between adherence and maternal viral load (mVL) in the mART arm. Results: Two thousand four hundred thirty-one mother–infant pairs were enrolled between 2011 and 2014; the baseline maternal median CD4 was 686 (IQR 553–869), and the median mVL was 322 copies/mL (IQR 40–1422). Self-reported adherence was lower in the mART arm compared with the iNVP arm (no missed doses within 4 weeks of all study visits: 66% vs 83%; within 2 weeks: 71% vs 85%; P < 0.0001). The iNVP adherence at week 6 was high in both arms: 97% in mART arm; 95% in iNVP arm. Time-to-event analyses showed that adherence to mART was associated with time to first mVL ≥400 copies/mL ( P < 0.0001). Missing 1 full day of doses over 3 days was associated with a 66% risk of mVL ≥1000 copies/mL (HR: 1.66; 95% CI: 1.37, 1.99). Conclusions: Postpartum women were less adherent to their own ART than mothers providing their infant's nevirapine prophylaxis. The self-reported missed mART doses were associated with high mVL. Strategies to optimize postpartum mART adherence are urgently needed. Clinical Trial Number: ClinicalTrials.gov: NCT01061151; closed to follow-up.